'We Do Much More Than Norms Require': Making Sense of Family-Owned Healthcare Firms' Profitability and Ethics. (December 2021) - Hiltunen, Esa; Holopainen, Riikka; Li, Kang
To address the literature gap regarding the business ethics of family firms in the healthcare sector, this case study investigates profitability and business ethics from the perspective of a very successful Finnish private healthcare company. The study combines business ethics and sensemaking theories to provide a broad view of the company's performance and stimulate new thinking about the relationship between ethics and profitability in private healthcare. Company's profitability requirements seem to elicit disapproval from the public. This study examines how a private, family-owned healthcare company combines business ethics and profitability successfully in its operations and how this family-owned company has successfully constructed a plausible, trusted and ethical identity. The theoretical framework of this study is based on business ethics, profitability, trust and sensemaking theory. The study shows that the case company has worked tirelessly to maintain high ethical practices and standards in providing excellent care and enjoying high profitability. By achieving high standards of business ethics and maintaining good social relations with stakeholders, the company has developed a plausible and trustworthy identity, while continuously improving its operations. The case shows that the surrounding environment, in particular, places significant pressure on the case company's daily activities and management. Even when customers (municipalities and residents) are very satisfied with the quality of care, this does not automatically lead to performance and profitability in the short term. Profitability as a value creation can also depend on personal relations and trust fostered between the company and its stakeholders. Thus, applying sensemaking theory, profitability means company's ongoing sensemaking about the plausibility of its actions and reading cues within the environment now and for the future.